THU0186 Infliximab VS Etanercept: the Importance of Immunogenicity and Serum Drug Monitoring in Clinical Practice. (10th June 2014) - Gainaru, C.; Diana, M.; Iliuta, M.; Luca, G.; Apetrei, N.; Constantinescu, C.; Groseanu, L.; Bojinca, V.; Saulescu, I.; Borangiu, A.; Balanescu, A.; Predeteanu, D.; et al.
Abstract : Background: Treatment with tumor necrosis factor (TNF) inhibitors in rheumatoid arthritis (RA) patients is based on the principle 'one size fits all', but different immunogenicity of these drugs has a profound effect on pharmacokinetics and clinical response [1]. Objectives: To measure infliximab (INF) and etanercept (ETA) drug level and presence of antidrug antibodies (ADAb) and to investigate clinical response and its relationship to drug immunogenicity and disease modifying anti-rheumatic drug (DMARD) association. Methods: Thirty nine patients with moderate or high disease activity RA, treated with INF or ETA were evaluated for 6 months. Their clinical characteristics, DMARD association and serum drug and ADAb level were measured at baseline. Clinical activity and improvement at 4 months were measured using DAS28 score and EULAR response criteria. Results: Ninety percent of patients treated with INF had concomitant DMARD, compared to 73.6% in ETA group. Eleven (45%) out of 20 patients treated with INF had ADAb: 7 patients had undetectable INF level, and 2 patients - subtherapeutic INF drug level. The presence of ADAb has correlated negatively with DMARD association in INF group (r=-0.492, P=0.027). In ETA treated patients, no ADAb were found. For both biologics, detectable drug level correlated with EULAR response at 4 months (for INF: r=0.701, P=0.001; for ETA: r=0.550, P=0.018). The association of a DMARD correlated with detectable serum INF (r=0.459, P=0.042) and a better EULAR response in patients treated with INF (r=0.468, P=0.038). Conclusions: Our study confirms the difference in anti TNF drug's immunogenicity and the importance of adding a DMARD to INF therapy. Also, therapeutic drug monitoring can be used to predict further clinical response. References: Meghna Jani, Anne Barton RBW et al. The role of DMARDs in reducing the immunogenicity of TNF inhibitors in chronic inflammatory diseases. Rheumatol. (Oxford, England) Augv14. 2013; Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4828